2004
DOI: 10.1073/pnas.0404073101
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase pathways defend against bacterial pore-forming toxins

Abstract: Cytolytic pore-forming toxins are important for the virulence of many disease-causing bacteria. How target cells molecularly respond to these toxins and whether or not they can mount a defense are poorly understood. By using microarrays, we demonstrate that the nematode Caenorhabditis elegans responds robustly to Cry5B, a member of the pore-forming Crystal toxin family made by Bacillus thuringiensis. This genomic response is distinct from that seen with a different stressor, the heavy metal cadmium. A p38 mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
390
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(405 citation statements)
references
References 22 publications
13
390
2
Order By: Relevance
“…Remarkably, the distinctive phenotypic changes associated with Cry1Ab cytotoxicity also can be blocked by inhibiting the AC͞PKA signaling pathway. Together, these results support the notion that cell death, occasioned by Cry toxins, is a complex cellular response and is not simply osmotic lysis (14,41).…”
Section: Discussionsupporting
confidence: 73%
“…Remarkably, the distinctive phenotypic changes associated with Cry1Ab cytotoxicity also can be blocked by inhibiting the AC͞PKA signaling pathway. Together, these results support the notion that cell death, occasioned by Cry toxins, is a complex cellular response and is not simply osmotic lysis (14,41).…”
Section: Discussionsupporting
confidence: 73%
“…In fact, recent studies with another member of the Cry toxin family, Cry5B, showed that exposure of cells to Cry toxin induces changes in a mitogen-activated protein kinase pathway and stimulates cellular defenses necessary in coping with toxin attack. 15 The high affinity and specific binding of Cry1Ab to BT-R 1 indicates that BT-R 1 , indeed, is the cell surface ligand recruited for targeting host cells. 31,50 BT-R 1 homologs are the principal determinant for Cry1A toxin action in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Instead, the interaction of toxins with cells involves complicated pathways, the end result of which is cell death. [15][16][17] The Cry proteins of Bacillus thuringiensis (Bt) represent more than 100 phylogenetically related toxins with varied entomopathogenic activities. 18 Like many other bacterial toxins, Cry toxins incorporate into lipid bilayer rafts as well as brush border membrane vesicles (BBMV).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent issue of PNAS, two key articles (4,5) provided compelling evidence that integrated signaling mechanisms involving components of both the PMK-1 and KGB-1 pathways are critical for the innate response of C. elegans to challenge either with whole bacteria or bacterial toxins. It appears that these responses are achieved by transcriptional and posttranslational regulation of MAPK pathway members.…”
Section: Invertebrate Innate Immune Responsesmentioning
confidence: 99%
“…With the idea of identifying transcriptional targets of MAPK signaling pathways that play a role in the primordial immune response in C. elegans, Huffman et al (4) embarked upon DNA microarray analysis to identify differentially regulated genes after exposure to bacteria expressing the Bacillus thuringensis Cry5B crystal pore-forming toxin (PFT). To distinguish these genes from others that lead to death of the organism, Huffman et al included a control treatment involving exposure to the heavy metal cadmium.…”
Section: The Transcriptome Of C Elegans Innate Immunitymentioning
confidence: 99%